The Students’ Religion Attitude: Study of Pesantren Ramadhan for Senior High School in Padang City - Hasan Zaini; Nofri Andy N; Hilma Pami Putri (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
The Padang City Government creates Pesantren Ramadhan activities as a media for fostering faith and devotion in forming character society. This article aims to analyze the role of students' religious attitudes after participating in Pesantren Ramadhan by analyzing applied learning patterns. This study used a descriptive analytical approach. The data derived from interviews and observations. The results of this study showed that: (1) Pesantren Ramadhan has been carried out for 12 times activities and has an impact on the way students behave in daily life and the application of religious practices is applied in a sustainable manner (2) Knowledge, belief, and understanding of religion become stimulation in increasing religious attitudes (3) The Padang City Government makes Pesantren Ramadhan as a media in forming the character of the young generation in order to have a noble character. Keywords: Students’ Religion Attitude, Pesantren Ramadhan, Learning Pattern